The conceptual design of novel future UAV's incorporating advanced technology research components - Clarke, Adrian James (Cranfield University, 2011)
There is at present some uncertainty as to what the roles and requirements of the next generation of UAVs might be and the configurations that might be adopted. The incorporation of technological features on these designs is also a significant driving force in their configuration, efficiency, performance abilities and operational requirements. The objective of this project is thus to provide some insight into what the next generation of technologies might be and what their impact would be on the rest of the aircraft. This work involved the conceptual designs of two new relevant full-scale UAVs which were used to integrate a select number of these advanced technologies. The project was a CASE award which was linked to the Flaviir research programme for advanced UAV technologies. Thus, the technologies investigated during this study were selected with respect to the objectives of the Flaviir project. These were either relative to those already being developed as course of the Flaviir project or others from elsewhere. As course of this project, two technologies have been identified and evaluated which fit this criterion and show potential for use on future aircraft. Thus we have been able to make a contirubtion knowledge in two gaps in current aerospace technology. The first of these studies was to investigate the feasibility of using a low cost mechanical thrust vectoring system as used on the X-31, to replace conventional control surfaces. This is an alternative to the fluidic thrust vectoring devices being proposed by the Flaviir project for this task. The second study is to investigate the use of fuel reformer based fuel cell system to supply power to an all-electric power train which will be a means of primary propulsion. A number of different fuels were investigated for such a system with methanol showing the greatest promise and has been shown to have a number of distinct advantages over the traditional fuel for fuel cells (hydrogen). Each of these technologies was integrated onto the baseline conceptual design which was identified as that most suitable to each technology. A UCAV configuration was selected for the thrust vectoring system while a MALE configuration was selected for the fuel cell propulsion system. Each aircraft was a new design which was developed specifically for the needs of this project. Analysis of these baseline configurations with and without the technologies allowed an assessment to be made of the viability of these technologies. The benefits of the thrust vectoring system were evaluated at take-off, cruise and landing. It showed no benefit at take-off and landing which was due to its location on the very aft of the airframe. At cruise, its performance and efficiency was shown to be comparable to that of a conventional configuration utilizing elevons and expected to be comparable to the fluidic devices developed by the Flaviir project. This system does however offer a number of benefits over many other nozzle configurations of improved stealth due to significant exhaust nozzle shielding.The fuel reformer based fuel cell system was evaluated in both all-electric and hybrid configurations. In the ell-electric configuration, the conventional turboprop engine was completely replaced with an all-electric powertrain. This system was shown to have an inferior fuel consumption compared to a turboprop engine and thus the hybrid system was conceived. In this system, the fuel cell is only used at loiter with the turboprop engine being retained for all other flight phases. For the same quantity of fuel, a reduction in loiter time of 24% was experienced (compared to the baseline turboprop) but such a system does have benefits of reduced emissions and IR signature. With further refinement, it is possible that the performance and efficiency of such a system could be further improved. In this project, two potential technologies were identified and thoroughly analysed. We are therefore able to say that the project objectives have been met and the project has proven worthwhile to the advancement of aerospace technology. Although these systems did not provide the desired results at this stage, they have shown the potential for improvement with further development.
Keywords: Thrust vectoring; fuel cells; fuel processing; alternative fuels; aircraft performance